(untitled) (Confluenţe Bibliologice, 2025)
The author refers to the book LOUIS PIERRE BLANC written by Oana Marinache and Cristian Gache, published by History of Art Publishing House in Bucharest in 2014 in Unforgettable Architects collection. Pierre Louis Blanc was born on December 31, 1860, in Geneva. He attended classes at Zürich Polytechnic. Swiss architect comes in Bucharest in early 1884 advised by Ion Mincu, his Romanian colleague. Among the main projects undertaken by architect Louis Pierre Blanc can be listed as follows: Botanical Institute in Bucharest; University of Iaşi; Faculty of Medicine in Bucharest etc.